Mapping ideological preferences in Brazilian elections, 1994-2018: A municipal-level study - Power, T; Rodrigues-Silveira, R (Brazilian Political Science Association, 2019)
This article investigates the electorally expressed ideology of Brazilian voters via ecological analysis at the municipal level between 1994 and 2018. Our purpose is to analyze the main conditioners of aggregated patterns of ideology measured at a high spatial resolution. We test four major explanations for the variation in ideology at the municipal level: the effect of incumbent alignments, social modernization, political pluralism, and social inclusion. We find that although the Brazilian electorate as a whole leans to the right, there has been a ‘gravitational effect’ exerted by presidential incumbents over local ideology, and during the PT years this was visible in municipal outcomes. However, the vast majority of municipalities tended to the right even during the period of PT national government. During the late Dilma Rousseff years there was a return to a more conservative vote-revealed ideology at the local level, with a sharper veer to the right in the 2016 municipal and 2018 federal elections under Michel Temer. Overall, when we examine local voting in PR elections, we observe that there was no durable electoral realignment in the period under study.